Childhood Malnutrition - Vassilakou, Tonia (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book covers a wide range of malnutrition manifestations across the globe. Malnutrition in any form has an serious, long-term impact on children's development, health and well-being. It is an emerging public health problem that needs to be addressed through actions and policies.The Special Issue opens with an overview of global malnutrition data. It is followed by three articles on eating disorders: a systematic review of the correlation between vegetarian diets and eating disorders in adolescents and young adults, a review of the nutritional risks among adolescent athletes with disordered eating, and a systematic review of the neuroimaging findings in adolescents and young adults with anorexia nervosa.The next article is a review on the nutritional status of pediatric cancer patients at diagnosis and its correlations with treatment, clinical outcome and long-term growth and health of survivors.The need for more extensive assessment of children' nutritional status in developing countries is explored in the next two articles: a presentation of anthropometry measurements among Nepali children living in orphanages and a report on the nutritional status, diet, and intestinal parasites in hosted Saharawi children.The next article focusses on the development of a disease-specific tool for determining malnutrition risk in pediatric and adolescent cystic fibrosis outpatients in Greece. The last two articles examine aspects of childhood obesity in two Mediterranean countries. First, sociodemographic determinants of childhood obesity in Spain are presented. The last article examines the effects of nutrition and physical activity habits and perceptions on adolescents' Body Mass Index in Greece.We wish to thank everyone who contributed to this project, including the patients and families that participated in the studies presented in this book.